Технология многослойных печатных плат - Федулова А. А. Антонина Арсентьевна; Устинов Ю. А. Юрий Александрович; Котов Е. П. Евгений Павлович; Шустов В. П. Владимир Петрович; Явич Э. Р. Эмиль Рафаелович (Москва, Радио и связь, 1990)
Авт. указаны на обороте тит. л.